2022
DOI: 10.1097/brs.0000000000004338
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Spine Surgery Navigation

Abstract: Study Design. Collectively, seven cadavers were instrumented with 124 thoracolumbar pedicle screws using VisAR augmented reality/guidance. Sixty-five screws were inserted into four donors using open dissection spine surgery. Fifty-nine screws were positioned in three donors with a minimally invasive spine surgery (MISS) procedure. For both open and MISS, VisAR was used exclusively for pedicle screw navigation.Objective. The objective of this study was to determine the accuracy of pedicle screw placement using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…This allows the surgeon to see a 3D image of the patient's spine with the skin intact and two-dimensional (2D) computed tomography (CT) images of the instruments' path and trajectory while looking directly at the surgical field (36) (Figure 3). Currently, wearable devices, such as HMD, have been commonly used to display AR views for ease and speed and to accomplish feasibility, accuracy, and safety in workflows from open cases to MISS (14,19). Current platforms include key features such as reducing attention shift from the surgical field to monitors, line-ofsight interruption, and cumulative exposure to ionizing radiation.…”
Section: Applications Of Ar In Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…This allows the surgeon to see a 3D image of the patient's spine with the skin intact and two-dimensional (2D) computed tomography (CT) images of the instruments' path and trajectory while looking directly at the surgical field (36) (Figure 3). Currently, wearable devices, such as HMD, have been commonly used to display AR views for ease and speed and to accomplish feasibility, accuracy, and safety in workflows from open cases to MISS (14,19). Current platforms include key features such as reducing attention shift from the surgical field to monitors, line-ofsight interruption, and cumulative exposure to ionizing radiation.…”
Section: Applications Of Ar In Surgerymentioning
confidence: 99%
“…Studies have reported that Xvision by Augmedics has pedicle screw accuracies greater than at least 97.7% (40). Felix et al compared pedicle screw accuracies between open and MISS procedures as both were guided by the AR system, VisAR (14). A total of 124 pedicle screws were inserted with VisAR navigation with 96% accuracy (Gertzbein-Robbins grades A and B), reporting that AR is an emerging technology can be highly accurate for both surgeries (14).…”
Section: Pedicle Screw Accuracy In Current Ar Platformsmentioning
confidence: 99%
See 3 more Smart Citations